2022
DOI: 10.1101/2022.05.05.490779
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Lymph node-targeted vaccine boosting of TCR-T cell therapy enhances anti-tumor function and eradicates solid tumors

Abstract: While T cell receptor (TCR)-modified T cell therapies have shown promise against solid tumors, overall therapeutic benefits in clinical practice have been modest due in part to suboptimal T cell persistence and activation in vivo, alongside the possibility of tumor antigen escape. In this study, we demonstrate an approach to enhance the in vivo persistence and activation of TCR-T cells through combination with Amphiphile (AMP)-vaccination including cognate TCR-T peptides. AMP-modification improves lymph node t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 52 publications
(105 reference statements)
0
3
0
Order By: Relevance
“…As a monotherapy, cancer vaccines have not yet been demonstrated to show outstanding clinical results in malignant tumor treatment. Recently, there has been a growing interest in the integration of cancer vaccines with ACTs to combat tumor evasion of immune surveillance and resistance ( 77 79 ). Ma et al ( 77 , 78 ) identified that cancer vaccination induces metabolic changes in CAR-T cells, leading to an increase in the production of interferon gamma (IFN-γ), which may potentially contribute to overcoming the immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…As a monotherapy, cancer vaccines have not yet been demonstrated to show outstanding clinical results in malignant tumor treatment. Recently, there has been a growing interest in the integration of cancer vaccines with ACTs to combat tumor evasion of immune surveillance and resistance ( 77 79 ). Ma et al ( 77 , 78 ) identified that cancer vaccination induces metabolic changes in CAR-T cells, leading to an increase in the production of interferon gamma (IFN-γ), which may potentially contribute to overcoming the immunosuppressive tumor microenvironment.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, the enhanced efficacy of CAR-T cells induced by tumor vaccination may be associated with DCs, including factors such as DCs recruitment, uptake of tumor antigens, and activation ( 77 , 78 ). In another study, researchers discovered that the combination of tumor vaccines with TCR-T cell therapy significantly enhanced the anti-tumor response of TCR-T cells and induced epitope spreading among the endogenous T cell population, leading to durable eradication of established solid tumors in syngeneic tumor models ( 79 ). The improved anti-tumor efficacy was associated with pro-inflammatory transcriptional reprogramming in lymph nodes and enhanced maturation of antigen presenting cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation